Impact of different cropping systems on structural attributes and aggregate-associated carbon dynamics of clayey soil under conservation agriculture - Kundu, Arnab; Dey Sarkar, Jayashree; Mukherjee, Subham; Nandi, Ramprasad; Saha, Subhadip; Bandyopadhyay, Prasanta Kumar; Sharma, Shalini (Frontiers in Sustainable Food Systems, 2025)
IntroductionConservation agriculture (CA) is promoted as a sustainable intensification strategy for improving soil structure and enhancing carbon sequestration. However, the influence of short-term CA interventions on soil aggregation and aggregate-associated carbon dynamics in heavy clayey soils remains inadequately understood.MethodsA field experiment was conducted over three years (2018–2021) on a Vertic Epiaquept soil (~60% clay) in West Bengal, India, using a split–split plot experimental design with three rice-based cropping systems [rice–mustard–black gram (RMuB), rice–wheat–green gram (RWG) and rice–lentil–fallow (RLF)] in main plots, three tillage systems [conventional tillage (CT), zero tillage (ZT), and reduced tillage (RT)] in sub-plots and three combinations of residue and nutrient treatments [0% rice residue+100% recommended dose of fertilizer (RDF) (R1), 100% residue+75% RDF fertilization (R2) and 50% residue + 75% RDF fertilization (R3)] in sub-sub plots.Results and discussionAfter eight cropping seasons, ZT showed the highest values of geometric mean diameter (GMD) and aggregate ratio (AR), which were 13.0 and 22.6% higher than the corresponding values of CT, and 7 and 20% higher than those of RT. R2 resulted in a 3 and 13% hike in GMD and AR, respectively, over R1. RWG showed a hike in soil organic carbon (SOC) over other cropping systems which further reduced the tensile strength of soil aggregates. Although significantly higher SOC is recorded in the silt + clay (S+C) fraction, the carbon (C) mass associated with coarse macroaggregates (CMac) demonstrated an increase of up to 1.70 times compared to the C mass of the rest of the fractions.ConclusionConjoint adoption of ZT and 100% rice residue was the best management practice for maintaining the structural attributes of the experimental soil. Further, the inclusion of a cereal along with a leguminous crop in a rice-based cropping system demonstrated the best outcome in terms of structural indices, SOC, and aggregate-associated C mass. The study underscores the importance of context-specific CA strategies tailored to cropping system diversity and edaphic conditions for improving soil quality and mitigating carbon loss in fine-textured soils of the eastern Indo-Gangetic Plains.